8th Symposium on Hemostasis: Translational and Basic Science Discoveries. Issue 141 (May 2016) - Margaritis, Paris; Key, Nigel S.
Abstract: It has been 14 years since the first symposium on hemostasis at UNC Chapel Hill that focused primarily on the tissue factor (TF) and Factor VIIa (FVIIa) biology, biochemistry and translational work for the treatment of bleeding. Concepts, mechanistic data and therapeutic agents have since emerged that permeate not only aspects of the TF and FVIIa functions, but also broader processes in hemostasis and thrombosis. These processes involve circulating proteins, receptors, cells and cellular components that interact within the coagulation system as well as with additional systems that are dysregulated in disorders seemingly unrelated to bleeding/thrombosis. The reviews in this symposium provide the research background to understand such interactions and integrations.